STRUCTURED PARAMETRIC OPTIMIZATION OF MULTIVARIABLE ROBUST CONTROL BASED ON GENETIC ALGORITHMS - Tunik, Anatoliy A.; Touat, Mohand Achour (Proceedings of National Aviation University (archive), 2008)
This paper is devoted to the parametric robust - optimization of the LQG- controller designed for multivariable flight control system. At the 1St stage LQG- regulator is designed using the separation theorem. At the 2nd stage this controller was parametrically optimized on the basis of -criterion using genetic algorithm to find the trade-off between the performance and robustness. The sensitivity theory is applied to reduce the number of parameters involved in the optimization procedure.